Uso de telepsiquiatría para apoyar la atención primaria de salud mental en el tratamiento de niños, niñas y adolescentes con vulneración de derechos: resultados preliminares - Irarrázaval D., Matías; Mundt, Adrian; Martínez D., Pablo; Fernández G., Olga; Rojas C., Graciela (Revista Hospital Clínico Universidad de Chile, 2019)
The aim of this study was to present preliminary results of a video-based consultation-liaison psychiatry service (telepsychiatry) to enhance the delivery of mental health services in primary health care (PHC) for institutionalized children and adolescents (ICA). A mixed-methods study was carried out at two PHC clinics in Quilpué, Chile, to assess the feasibility of a telepsychiatry service (TPS). TPS consisted of bimonthly, remotely conducted video-conference sessions between PHC teams and child and adolescent consultant psychiatrists located at the Psychiatric University Hospital in Santiago, to discuss mental health problems of ICA. During July to December 2018 thirteen TPS sessions were carried out, and a total of 15 ICA were discussed to elaborate diagnostic and/or therapeutic recommendations. The intervention was useful and acceptable to PHC providers. Participants perceived that better coordination between substitute care facilities and PHC clinics would be useful, and that training opportunities to address the mental health needs of ICA were required. A TPS to enhance the delivery of mental health services in PHC for ICA was feasible, further studies are needed to determine benefits for ICA.